Development of an Observational Instrument to Assess Gastro-Esophageal Reflux Disease in Premature Infants - Öhman, Susanne Georgsson; Sandberg, Christina (International Journal of Child Health and Nutrition, 2014)
Background: Premature infants are at increased risk of developing Gastroesophageal Reflux Disease (GERD), which for these children is associated with a number of severe symptoms. There is great need for effective instruments and clear symptom criteria to assess the presence and degree of severity of GERD. Aim: To develop and pilot test an observation instrument for early detection of symptoms of GERD in premature infants. Method: A combination of three research methods was used – systematic literature review, observation instrument development and a pilot test. Results: The systematic review identified specific symptoms of GERD. The development of the observational instrument started with the establishment of concordance between the criteria of symptoms according to the literature review and to NIDCAP, “Newborn Individualized Developmental Care and Assessment Program”. In the pilot test the criteria of symptoms were revised by comparing the result and the criteria between infants that clinically were estimated to have had a reflux problem and the ones who did not. Conclusion: An observation instrument was developed. The clinical evaluation by a pilot test showed that the instrument could be useful to record significant symptoms and combinations of symptoms that may occur in premature infants assessed as having reflux problems.